PENERAPAN AKUNTANSI DAN KESESUAIANNYA DENGAN SAK ETAP PADA UMKM KOTA TEGAL - Hetika Hetika; Nurul Mahmudah (Politeknik Negeri Batam, 2017)
Small and Medium Enterprises (SMEs) have a very important role for the economy of Indonesia, especially the economy of Tegal City, because the development of SMEs in Tegal City increases the absorption of the highest labor force compared with other business units. This study aims to analyze the application of accounting at SMEs in Tegal City and to determine whether SMEs in Tegal City have prepared financial statements in accordance with Financial Accounting Standards Entities Without Public Accountabulity (SAK ETAP). The sample of this research is SMEs in Tegal city taken by purposive sample technique. Methods of data collection in this study used the method of observation with questionnaires and direct interviews with respondents. This study uses descriptive analysis techniques to determine the application of accounting in the preparation of financial statements of SMEs in the City of Tegal. The results showed that the implementation of accounting conducted by the perpetrators of SMEs in the city of Tegal is still very simple and the perpetrators of SMEs in the city of Tegal has not prepared financial statements in accordance with SAK ETAP due to lack of knowledge of SMEs regarding SAK ETAP.